The Human Development Bonus - Vayas, Tatiana (2014)
Analysis of the Human Development Bond at the national level and Tungurahua during the period January-June 2014. DOI: https://doi.org/10.31164/bcoyu.3.2014.553 URL: http://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/553